RESISTED VERSUS FASCINATED: THE MUSLIM-CHRISTIAN RELATIONSHIP IN THE POST-REGIONAL AUTONOMY IN PADANG, WEST SUMATERA - Andri Ashadi; Nurus Shalihin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
Christian students' involvement in the school Islamic programs such as wearing Muslim clothing, participating in the seven-minute Islamic sermon, and joining Islamic classes are often considered a compliance attitude. Instead, it is a process of self-adaptation because they attend a school within a Muslim majority environment.  Moreover, this camouflage represents their resistance to the school rules. This article discusses how Christian students in two state schools in Padang behave in the framework of Islamic customs. Based on the theories of Jean Baudrillard's simulacra and James C. Scott's resistance, the results of this study show that Christian students in two state schools in Padang tend to be obedient and interested in Islamic practices. For instance, they imitate the way Muslim students dress so that they look similar to Muslim students. This attitude pleases their Muslim teachers and fellow students. In addition, Minang people in their neighborhood also amaze and always refer to these Christian students€™ attitude as a model to be followed.